A review of Trachusoides Michener and Griswold (Hymenoptera: Megachilidae) - Griswold, Terry (Zootaxa, 2015)
The rare genus Trachusoides, previously known only from a single species inhabiting the Western Ghats of India, is reviewed. Trachusoides elsieae, new species, is described from Laos, additional records for T. simplex are documented, and a key to separate the species is provided.